BEST PRACTISE UPAYA PENINGKATAN KETUNTASAN BELAJAR SISWA DENGAN METODE C3T DAN TUTOR SEBAYA - ELSA WIDJAJANTI NURWIJANI (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2021)
The impression of science subjects as difficult and boring lessons has an impact on the lack of motivation in doing math problems. This results in the low achievement of student learning mastery. This activity focuses on the implementation of the C3T method and peer tutoring in an effort to improve students' science learning mastery, in class VIII MTsN 14 Jombang. The results of the activity showed an increase in the learning mastery of class VIII MTsN 14 Jombang students from 6 students to 28 students. The C3T method as a method that emphasizes students to play an active, fast and intelligent role in learning is proven to be able to increase the motivation of all students so that complete learning can be achieved. The peer tutoring method fosters the self-confidence of students who become peer tutors and a sense of togetherness for students who have not yet completed. ABSTRAKKesan mata pelajaran IPA sebagai pelajaran yang sulit dan membosankan membawa dampak pada kurangnya motivasi dalam mengerjakan soal IPA hitungan. Hal tersebut berakibat pada rendahnya pencapaian ketuntasan belajar siswa. Kegiatan ini berfokus pada implementasi metode C3T dan tutor sebaya dalam upaya meningkatkan ketuntasan belajar IPA siswa, di kelas VIII MTsN 14 Jombang. Hasil kegiatan menunjukkan adanya peningkatan ketuntasan belajar siswa kelas VIII MTsN 14 Jombang dari 6 siswa menjadi 28 siswa. Metode C3T sebagai metode yang menekankan peserta didik untuk berperan aktif, cepat dan cerdas dalam pembelajaran terbukti mampu menambah motivasi seluruh siswa sehingga ketuntasan belajar bisa tercapai. Metode tutor sebaya menumbuhkan rasa percaya diri siswa yang menjadi tutor sebaya dan rasa kebersamaan bagi siswa yang belum tuntas.